Divergent effects of itaconate isomers on Coxiella burnetii growth in macrophages and in axenic culture - Siddique, Md Nur A Alam; Kellermeier, Fabian; Ölke, Martha; Zhao, Mingming; Büssow, Konrad; Oefner, Peter J.; Lührmann, Anja; Dettmer, Katja; Lang, Roland (Frontiers in Immunology, 2024)
Aconitate decarboxylase-1 (ACOD1) is expressed by activated macrophages and generates itaconate that exerts anti-microbial and immunoregulatory effects. ACOD1-itaconate is essential for macrophage-mediated control of the intracellular pathogen Coxiella (C.) burnetii, which causes Q fever. Two isomers of itaconate, mesaconate and citraconate, have overlapping yet distinct activity on macrophage metabolism and inflammatory gene expression. Here, we found that all three isomers inhibited the growth of C. burnetii in axenic culture in ACCM-2 medium. However, only itaconate reduced C. burnetii replication efficiently in Acod1 -/-macrophages. In contrast, addition of citraconate strongly increased C. burnetii replication in Acod1 +/-macrophages, whereas mesaconate weakly enhanced bacterial burden in Acod1 -/-macrophages. Analysis of intracellular isomers showed that exogenous citraconate and mesaconate inhibited the generation of itaconate by infected Acod1 +/-macrophages.Uptake of added isomers into Acod1 -/-macrophages was increased after infection for itaconate and mesaconate, but not for citraconate. Mesaconate, but not citraconate, competed with itaconate for uptake into macrophages. Taken together, inhibition of itaconate generation by macrophages and interference with the uptake of extracellular itaconate could be identified as potential mechanisms behind the divergent effects of citraconate and mesaconate on C. burnetii replication in macrophages or in axenic culture.